Food insecurity, food assistance, and physical and cognitive functioning among older Americans - Usha Dhakal; Khalil El Asmar; Carlos F. Mendes deLeon (PLoS ONE, 2025)
Introduction Food insecurity is associated with adverse late-life health outcomes, including disability, dementia, and mortality. But its role in changes in physical and cognitive functioning remains unclear, as does the impact of food assistance. Methods We used weighted generalized estimating equations to investigate the association between food insecurity, food assistance, and physical and cognitive functioning among US adults aged 50 years and older (n = 6489). Using 2014 Health and Retirement Study (HRS) wave as the baseline, we extracted individual-level data from a HRS subsample from the 2013 Health Care and Nutrition Study and linked it to three additional HRS waves through 2020. This study included two outcome measures. First, physical functioning, a summary score of nine items that assessed difficulties in performing everyday physical activities (range 0–9), with higher scores indicating lower physical functioning. Second cognitive functioning, a composite score based on four cognitive tasks (range 0–27), with higher scores indicating better cognitive functioning. Results In fully adjusted models, greater food insecurity was associated with lower physical functioning at baseline (β = 0.074 [95% CI 0.019, 0.129]) and showed marginal evidence of higher decline over time (0.010 [0.000, 0.020], p = .058). Food assistance was only associated with baseline physical functioning (−0·011 [−0·047, 0·025]). The triple interaction between food insecurity, food assistance, and time suggested that food assistance may attenuate declines in physical functioning (−0.014 [−0.030, 0.002], p = .078). Greater food insecurity (−0.206 [−0.305, −0.107]) and food assistance (−1.215 [−1.582, −0.848]) were associated with lower baseline cognitive functioning, but neither was associated with change over time. Food assistance did not moderate the association between food insecurity and changes in cognitive functioning over time. Conclusions Food insecurity is associated with poorer physical and cognitive functioning in older adults. Strengthening policies and strategies that promote food assistance participation may help mitigate declines in physical functioning and improve health outcomes among older adults.